Match each expression with an equivalent expression.

Question 4 options:

6x−4y

6−4x

6x−4x

6x−4

1. 2x
2. 2(3x−2)
3. 2(3−2x)
4. 2(3x−2y)

Respuesta :

Answer:

[tex]6x-4y[/tex] →  4.  [tex]2(3x-2y)[/tex]

[tex]6-4x[/tex] →    3.  [tex]2(3-2x)[/tex]

[tex]6x-4x[/tex] →  1. [tex]2x[/tex]

[tex]6x-4[/tex] →   2. [tex]2(3x-2)[/tex]

Step-by-step explanation:

You need to:

 Factor out 2 from [tex]6x-4y[/tex],  then you get the equivalent expression:

[tex]=2(3x-2y)[/tex] this matches with OPTION 4

Factor out 2 from [tex]6-4y[/tex], then you get the equivalent expression:

[tex]=2(3-2x)[/tex] this matches with OPTION 3

Make the subtraction for [tex]6x-4x[/tex],  then you get the equivalent expression:

[tex]=2x[/tex] this matches with OPTION 1

Factor out 2 from [tex]6x-4[/tex],  then you get the equivalent expression:

[tex]=2(3x-2)[/tex] this matches with OPTION 2

Answer:

6x-4y=2(3x-2y),

6-4x=2(3-2x),

6x-4x=2x,

6x-4=2(3x-2)

Step-by-step explanation:

We have been given 4 expressions

6x−4y, 6−4x, 6x−4x, 6x−4

Now we need to simplify or factor so that we can match each expression with an equivalent expression.

6x-4y=2(3x-2y)

6-4x=2(3-2x)

6x-4x=2x

6x-4=2(3x-2)

Now we can easily see that right side is unique for each of the given expression which can be easily matched with given choices.